PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP BIAYA EKUITAS DAN BIAYA UTANG - Dian Antika Sari; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
BSTRACTThis study aims to examine the effect of corporate governance on cost ofequity and cost of debt. Elements of corporate governance used are corporategovernance index, effectiveness of board commissioners, and effectiveness of auditcommittee. The samples of this study are 40 public companies listed on CorporateGovernance Perception Index (CGPI) for period 2012-2015.The result of this study show that the quality of corporate governance asmeasured by corporate governance index have a signicant negative impact on cost ofequity and cost of debt. The effectiveness of board commissioners has a significantnegative effect on cost of equity and cost of debt. The effectiveness of audit committeehas a significant negative effect on cost of equity and cost of debt.Keywords: corporate governance index, the effectiveness of board commissioners,the effectiveness of committee audit, cost of equity, cost of debt